DESIGN OF BOUTIQUE HOTEL IN LAKE SIOMBAK TOURISM AREA WITH INSTAGRAMABLE RECREATION FACILITIES: DESIGN OF BOUTIQUE HOTEL IN LAKE SIOMBAK TOURISM AREA WITH INSTAGRAMABLE RECREATION FACILITIES - Chairani, Nabila (Talenta Publisher, 2022)
Tourism is the largest foreign exchange-producing sector in Indonesia, while the most developed is natural tourism. Lake Siombak is a nature-based tourism in Medan Marelan District which is currently growing because of its considerable potential in the future. However, based on BPS data from the Medan Marelan District (2019), there are no lodging facilities in tourist areas in Medan Marelan. Even though these facilities can improve tourism services, especially for tourists from outside the region, especially if the facilities are modern and Instagramable. For that, what are the criteria for Instagramable tourism facilities? And how to design and apply the criteria for Instagramable tourism facilities into the design of Boutique Hotels in the Lake Siombak tourist area?. The method used to answer the design questions uses qualitative analysis methods in the form of observations, interviews and literature. So the result is a Boutique Hotel design with Instagramable architecture which has a unique building design with a Lake Siombak landscape which is a plus for this boutique hotel and is equipped with recreational facilities such as swimming pools, outdoor dining areas, playgrounds, piers and many photo spot areas that can be used as background for taking selfies of visitors.